2023
DOI: 10.1007/s00415-023-11973-y
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B reactivation is a rare event among patients with resolved infection undergoing anti-CD20 antibodies in monotherapy without antiviral prophylaxis: results from the HEBEM study

Blanca Marzo,
Angela Vidal-Jordana,
Joaquín Castilló
et al.

Abstract: Introduction Prospective data on the risk of hepatitis B reactivation (HBVr) among patients with resolved HBV infection undergoing anti-CD20 antibodies monotherapy is scarce. We aimed to assess the risk of HBVr in patients with resolved HBV infection treated with rituximab or ocrelizumab in monotherapy for multiple sclerosis (MS) or neuromyelitis optica spectrum disorder (NMOSD) without antiviral prophylaxis. Methods HEBEM is a prospective study that inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In Spain, a cohort of 540 patients using anti-CD20 drugs was followed for a median duration of 3.1 years. Among six patients at risk for HBV reactivation and using ocrelizumab, no cases of reactivation were observed during their follow-up [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Spain, a cohort of 540 patients using anti-CD20 drugs was followed for a median duration of 3.1 years. Among six patients at risk for HBV reactivation and using ocrelizumab, no cases of reactivation were observed during their follow-up [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, two out of the three patients who experienced reactivation had anti-HBs levels below 100 mUI/mL, and one had anti-HBs negativity. In the Spanish study, which included 28 patients (22 rituximab, 6 ocrelizumab), the median anti-HBs level was determined as 105.5 mIU/L (range: 0–609.3), and no instances of reactivation were observed [ 18 ]. In the study conducted in Italy, no significant difference in reactivation was observed between patients with anti-HBs titers < 100 and > 100 mUI/mL.…”
Section: Discussionmentioning
confidence: 99%